Adopting an external focus of attention alters intracortical inhibition within the primary motor cortex - Kuhn, Y.‐A.; Keller, M.; Ruffieux, J.; Taube, W. (Acta Physiologica, 2017)
Aim Although it is well established that an external (EF) compared to an internal (IF) or neutral focus of attention enhances motor performance, little is known about the underlying neural mechanisms. This study aimed to clarify whether the focus of attention influences not only motor performance but also activity of the primary motor cortex (M1) when executing identical fatiguing tasks of the right index finger (first dorsal interosseous). Transcranial magnetic stimulation (TMS) at intensities below motor threshold was applied over M1 to assess and compare the excitability of intracortical inhibitory circuits. Methods In session 1, 14 subjects performed an isometric finger abduction at 30% of their maximal force to measure the time to task failure (TTF) with either an IF or EF. In session 2, the same task was performed with the other focus. In sessions 3 and 4, subthreshold TMS (subTMS) and paired‐pulse TMS were applied to the contralateral M1 to compare the activity of cortical inhibitory circuits within M1 during EF and IF. Results With an EF, TTF was significantly prolonged (P = 0.01), subTMS‐induced electromyographical suppression enhanced (P = 0.001) and short‐interval intracortical inhibition (SICI) increased (P = 0.004). Conclusion The level of intracortical inhibition was previously shown to influence motor performance. Our data shed new light on the ability to instantly modulate the activity of inhibitory circuits within M1 by changing the type of attentional focus. The increased inhibition with EF might contribute to the better movement efficiency, which is generally associated with focusing externally.